PERILAKU BULLYING SECARA VERBAL DALAM INTERAKSI SOSIAL ANAK DI SEKOLAH DASAR - Eka Suci Ramadhita, Renata; Jenal Mutaqin, Ejen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This reasearch examines a case study of verbal bullying behavior in an elementary schools. It can negatively impact student victims, especially their emotional and psychological well-being. The approach used in this study was descriptive qualitative. The aim of this research was to describe the occurrence of verbal bullying behavior within the school environment. Data collection was conducted through observation, interviews, and documentation. The findings indicate that verbal bullying is frequently found in elementary schools in the form of mockery, insults, and inappropriate remarks. Many students experience or witness this behavior, which leads to psychological impacts such as decreased self-confidence. Social and economic conditions influence the emergence of verbal bullying behavior. Therefore, preventive measures by teachers and parents are necessary.